"A Place Thriving With History": Reclaiming Narratives About Literacy in the Arkansas Ozarks. Issue 4 (22nd August 2016) - Connors, Sean P.
Abstract: Building on scholarship that emphasizes a relationship between critical literacy and place‐conscious pedagogy, this article describes a community inquiry project that asked undergraduates in an introductory literacy studies course to use oral histories that they collected from people in the Arkansas Ozark region to engage in placemaking and reclaim narratives about literacy in the area where they lived. The Literacy in Ozark Lives project challenged the students to examine the oral histories with an eye toward identifying people and institutions that sponsored their interviewees' experiences with reading and writing, and explaining how social and economic transformations in the region shaped the purpose of their interviewees' literacy. To conclude the project, the students produced digital video essays intended to complicate problematic cultural models that promote a deficit view of people and literacy in the U.S. South, particularly the Arkansas Ozark region.